ChemInform Abstract: Muraymycin Nucleoside‐Peptide Antibiotics: Uridine‐Derived Natural Products as Lead Structures for the Development of Novel Antibacterial Agents. Issue 22 (12th May 2016) - Wiegmann, Daniel; Koppermann, Stefan; Wirth, Marius; Niro, Giuliana; Leyerer, Kristin; Ducho, Christian
Abstract: Review: [129 refs.